2000
DOI: 10.1002/1099-0496(200009)30:3<249::aid-ppul9>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of congenital diaphragmatic hernia

Abstract: The outcome of congenital diaphragmatic hernia (CDH) differs for different stages of the fetus or infant's life (i.e., antenatal, immediate postnatal, and postoperative). Assessing combined data from nonrandomized studies is technically difficult. Following recognized methods of reviewing such trials, we aimed to review the available literature on the outcome of CDH to provide a guide to clinicians when counselling parents who have a fetus/infant with this condition. Thirty-five studies reporting data for CDH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
42
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 42 publications
2
42
0
1
Order By: Relevance
“…This likely reflects the fact that the combined degree of pulmonary hypoplasia and pulmonary hypertension determine survival rate. 1,3 Although there were slight changes in our protocol for managing patients with CDH over the last 10 years, particularly with respect to the use of gentle ventilation, these did not affect outcome to any great degree, which remained relatively stable over the 10-year study period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This likely reflects the fact that the combined degree of pulmonary hypoplasia and pulmonary hypertension determine survival rate. 1,3 Although there were slight changes in our protocol for managing patients with CDH over the last 10 years, particularly with respect to the use of gentle ventilation, these did not affect outcome to any great degree, which remained relatively stable over the 10-year study period.…”
Section: Discussionmentioning
confidence: 99%
“…1 The timing in which surgery is performed has generated significant controversy, as many surgeons have gradually shifted away from performing an emergent repair, and instead emphasize the importance of waiting 48 hours or more for the "honeymoon period" to elapse. 2 However, survival of infants with CDH may be influenced to a greater degree by physiologic parameters that reflect the degree of pulmonary hypoplasia, thereby minimizing the overall importance of the timing of repair on survival.…”
mentioning
confidence: 99%
“…This anomaly carries a significant mortality of 40% to 60% [7][8][9][10][11][12]. The most severely affected fetuses with left CDH can be identified by a diagnosis at less than 25 weeks' gestational age, the presence of liver herniated into the hemithorax, and a low lung-tohead ratio (LHR) of less than 1.4 [13,14].…”
mentioning
confidence: 99%
“…Despite recent advances in medical and surgical management, the prognosis of such neonates continues to be uncertain because of persisting lung hypoplasia and pulmonary hypertension. 1,2 However, long-term cardiopulmonary sequelae of CDH survivors are still unclear, and understanding of developmental processes of hypoplasic lung is limited. 3 In the last decades, several studies reported the presence of persisting pulmonary abnormalities in a minority of CDH survivors, 4-8 but recent improvement in treatment led to survival of more severely affected infants, and little is known about these patients.…”
mentioning
confidence: 99%